Adaptation pressures during global decline on system transformation and its spatial consequences in China - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, 2011)
With the implementation of the approach of the Interactive Party-State model (Csan di, 2006, 2011) the paper demonstrates the possible short and long term consequences of the adaptation pressures exerted by the global crisis on Chinese system transformation. It points to the short term character of the crisis. It reveals the temporary slow-down of transformation as a reaction to adaptation pressures and its reversibility with the waning of the crisis. It describes the sensitivity of government reactions to crisis. It points to government's bias towards the construction industry, state owned and large enterprises with domestic trade orientation. It suggests the dynamizing effect of biased state intervention on manufacturing sector, overwhelmingly composed by small and medium sized privately owned enterprises. It comments the long-term consequences of this mismatch. It also argues that temporary slow-down of economic transformation owing to state interventions preserved party legitimacy. The paper sheds light on the spatial disparities of the impact, the reactions and of their respective consequences.
Keywords: F5; D78; R58; J08; O15; E24; 330; party-state model; short-term shocks; system transformation; global crisis; migration; economic policy reactions; prefectures; spatial disparities; Systemtransformation; Finanzkrise; Wirtschaftskrise; Wirkungsanalyse; Wirtschaftspolitik; Räumliche Verteilung; China